Netback pricing as a remedy for the Russian gas deficit - Marina Tsygankova (Statistics Norway, Research Department, 2008)
This descriptive study discusses the effects of increases in domestic gas prices on the Russian gas market. Domestic natural gas prices have remained below their long-run marginal cost for more than a decade since Russia's movement toward a market economy in 1991. As a result, the ability of the Russian gas sector to meet future growing demand from domestic and foreign consumers has come under question. In an attempt to avoid gas shortages in the future, Russian government wishes to introduce netback pricing of natural gas after 2011. Netback pricing refers to the process of equalizing the gas price in Russia to the gas price in Europe after adjusting for export taxes, transportation costs, and transit tariffs. The paper concludes that netback pricing can help Russia to avoid a gas deficit. However, the gas supply in Russia will remain tight until 2011. The downside of netback pricing is that it increases the ability of Gazprom to strengthen its control over the Russian gas industry.
Keywords: D40; L11; Q31; Q38; 330; Russia; natural gas; netback price; supply shortage; deficit